2018
DOI: 10.1002/anie.201808003
|View full text |Cite
|
Sign up to set email alerts
|

Living Coordination Polymerization of a Six‐Five Bicyclic Lactone to Produce Completely Recyclable Polyester

Abstract: The development of chemically recyclable polymers promises a closed-loop approach towards a circular plastic economy but still faces challenges in structure/property diversity and depolymerization selectivity. Here we report the first successful coordination ring-opening polymerization of 4,5-trans-cyclohexyl-fused γ-butyrolactone (M1) with lanthanide catalysts at room temperature, producing P(M1) with M up to 89 kg mol , high thermal stability, and a linear or cyclic topology. The same catalyst also catalyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
100
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 50 publications
(38 reference statements)
3
100
1
1
Order By: Relevance
“…Although the macrocycles obtained from these REPs retained the reactive moiety of the initiator and needed another step for deactivation, Grubbs and co‐workers have subsequently reported an REP based on olefin metathesis using cyclic olefin as the monomer and cyclic Ru complex as the initiator, which can be easily separated from the afforded polyolefin by reprecipitation . Since these pioneering works, various REP systems have been reported, such as anionic polymerization of cyclic esters using N ‐heterocyclic carbene initiator, cationic polymerization of vinyl ethers using cyclic hemiacetal ester initiator, nitroxyl radical‐mediated polymerization of styrene using cyclic nitroxide initiator, and coordination polymerization of terminal alkynes, olefins, and lactones as monomers using certain metal complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the macrocycles obtained from these REPs retained the reactive moiety of the initiator and needed another step for deactivation, Grubbs and co‐workers have subsequently reported an REP based on olefin metathesis using cyclic olefin as the monomer and cyclic Ru complex as the initiator, which can be easily separated from the afforded polyolefin by reprecipitation . Since these pioneering works, various REP systems have been reported, such as anionic polymerization of cyclic esters using N ‐heterocyclic carbene initiator, cationic polymerization of vinyl ethers using cyclic hemiacetal ester initiator, nitroxyl radical‐mediated polymerization of styrene using cyclic nitroxide initiator, and coordination polymerization of terminal alkynes, olefins, and lactones as monomers using certain metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the various REP systems reported to date, there are limited reports of controlled REP to produce well-defined cyclic polymers with narrow polydispersity. [25][26][27][28][32][33][34][35] Recently, Kudo and Nishikubo have reported that thiazolidine-2,4-dione (TZD), a cyclic aliphatic carbamate thioester, effectively works as the cyclic initiator for controlled REP of thiiranes to afford cyclic polysulfides with relatively narrow polydispersity of 1.2-1.4, 35 based on the controlled acyltransfer polymerization of thiiranes developed by Kameyama and Nishikubo. [36][37][38] The TZD-initiated REP system was further investigated in detail and applied to a functional molecular system by Vana and co-workers.…”
mentioning
confidence: 99%
“…Chemically recyclable polymers [1][2][3][4][5][6][7][8][9][10][11][12][13] have lately attracted growing attention because their building block chemicals,o r monomers,c an be recovered for the production of virgin plastics with the same qualities as the original, thus offering af easible solution to the end-of-use issue of polymeric materials and providing ac losed-loop approach towards acircular materials economy. [14] However, there is aparadox between the ability to depolymerize and performance,where polymers that can be readily depolymerized back to monomers often lack physical properties and mechanical strengths to be widely useful, and vice versa.…”
mentioning
confidence: 99%
“…Chemically recyclable polymers have lately attracted growing attention because their building block chemicals, or monomers, can be recovered for the production of virgin plastics with the same qualities as the original, thus offering a feasible solution to the end‐of‐use issue of polymeric materials and providing a closed‐loop approach towards a circular materials economy . However, there is a paradox between the ability to depolymerize and performance, where polymers that can be readily depolymerized back to monomers often lack physical properties and mechanical strengths to be widely useful, and vice versa.…”
Section: Methodsmentioning
confidence: 99%